ISO & Agent
Provides information for independent sales organizations. Covers processors, Point-of-sale equipment, card organizations, such as Visa, MasterCard, American Express, Discover and JCB, cardholder use of credit and debit cards, emerging alternative payment methods (ACH, Check 21, biometrics and others), emerging vertical markets (QSRs, FSAs, mobile, micropayments and others), security and PCI compliance and new and changing markets.